0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
0 like 0 dislike
Well arccos(–*θ*) = π – arccos(*θ*), so we have that    
arccos(cos*c*) = *c* =  arccos(-1/2) = π – arccos(1/2) = π – π/3
0 like 0 dislike
0 like 0 dislike
The reference angle=pi/3.

Cosine is negative in Q2 and Q3.

This is a triangle, so C must be in Q2.

In Q2, θ=pi-θref

C=pi-pi/3=2pi/3

No related questions found

33.4k questions

135k answers

0 comments

33.7k users

OhhAskMe is a math solving hub where high school and university students ask and answer loads of math questions, discuss the latest in math, and share their knowledge. It’s 100% free!